Scraping Therapy Improved Muscle Regeneration through Regulating GLUT4/Glycolytic and AMPK/mTOR/4EBP1 Pathways in Rats with Lumbar Multifidus Injury - Bin Zou; Juan Du; Qiwen Xuan; Yajing Wang; Zixiao Wang; Wen Zhang; Lianghua Wang; Wei Gu (Pain Research and Management)
Background. High morbidity of nonspecific low back pain (NLBP) and large consumption of medical resources caused by it have become a heavy social burden. There are many factors inducing NLBP, among which the damage and atrophy of multifidus (MF) are most closely related to NLBP. Scraping therapy can have significant treatment effects on NLBP with fewer adverse reactions and less medical fund input than other modalities or medications. However, the mechanism of scraping therapy treating NLBP remains unclarified. Here, we wanted to investigate the effects of scraping therapy on promoting MF regeneration and the underlying mechanisms. Methods. A total of 54 male rats (SD, 6-7 weeks old) were randomly divided into nine groups, namely, K, M6h, M1d, M2d, M3d, G6h, G1d, G2d, and G3d, with six rats in each group. They were injected with bupivacaine (BPVC) to intentionally induce MF injury. We then performed scraping therapy on the rats that had been randomly chosen and compared treatment effects at different time points. In vitro data including skin temperature and tactile allodynia threshold were collected and histological sections were analyzed. mRNA sequencing was applied to distinguish the genes or signaling pathways that had been altered due to scraping therapy, and the results were further verified through reverse transcription polymerase chain reaction and Western blot analysis. Results. Transitory petechiae and ecchymosis both on and beneath the rats’ skin raised by scraping therapy gradually faded in about 3 d. Cross-sectional area (CSA) of MF was significantly smaller 30 h, 2 d, and 4 d after modeling (P=0.007, P=0.001, and P=0.015, respectively, vs. the blank group) and was significantly larger in the scraping group 1 d after treatment (P=0.002 vs. the model 1d group). Skin temperature significantly increased immediately after scraping (P<0.001) and hindlimb pain threshold increased on the 2nd day after scraping (P=0.046 and P=0.028, respectively). 391 differentially expressed genes and 8 signaling pathways were characterized 6 h after scraping; only 3 differentially expressed genes and 3 signaling pathways were screened out 2 d after treatment. The amounts of mRNAs or proteins for GLUT4, HK2, PFKM, PKM, LDHA (which belong to the GLUT4/glycolytic pathway), p-mTOR, p-4EBP1 (which belong to the AMPK/mTOR/4EBP1 pathway), and BDH1 were enhanced, and p-AMPKα was decreased after scraping therapy. Conclusions. Scraping therapy has therapeutic effects on rats with multifidus injury by promoting muscle regeneration via regulating GLUT4/glycolytic and AMPK/mTOR/4EBP1 signaling pathways.